Pengaruh Literasi Keuangan dan Kualitas Laporan Keuangan Terhadap Kinerja UMKM - Gede Mandirta Tama; Ida Ayu Gede Danika Esa Pradnyani (AKUNTANSI 45, 2025)
The purpose of this research is to find out how the Endek Fabric Weaving Center's micro, small, and medium-sized enterprises (MSMEs) in Kalianget Village, Seririt District, Buleleng Regency do when it comes to financial literacy and the accuracy of their financial records. Endek Fabric Weaving Center's micro, small, and medium-sized enterprise (MSME) performance is the dependent variable in this research, which also examines financial literacy and the quality of financial statements as independent factors. Thirty offenders and weavers from Kalianget Village make up the study's population and sample. This study found that small and medium-sized enterprises (SMEs) in Endek fabric weaving centres are more likely to succeed when their owners are financially literate. Financial report quality also has a positive and significant effect on SMEs' performance. Lastly, SMEs in Kalianget Village are even more likely to succeed when their owners are financially literate and have high-quality financial reports